The eloquence of “placing the apparent in the place of the pronoun” and its purposes"Surat Al-Baqarah" as example (Damascus University Journal for legal sciences, 2025)
This research sheds light on a type of rhetorical deviation in the Qur’anic style, which is a departure from the apparent requirement of putting the pronoun in its place to mention the apparent instead of it, which is known in Arabic rhetoric's as “placing the apparent in the place of the pronoun,” explaining the reasons for the reversal in it and its revelant examples in Surat Al-Baqarah through the use of the descriptive analytical method based on tracing the places in which the divine statement has been modified when the pronoun has been mentioned and it put the apparent name in its place, and trying to find out the reasons for this deviation and its impact on Quran interpretation.The commentators varied in dealing with the departure from the apparent requirement by “placing the apparent in the place of the pronoun” and its reasons in their exegeses.It was evident through this research that the deviation has been plenty so that  explain the reason for the ruling, and it was found that placing the apparent in the place of the pronoun in the end of the verse often follows the course of the proverb.
Keywords: Deviation; placing the apparent in the place of the pronoun; the apparent; the pronoun; Pronoun reference